2014
DOI: 10.4161/hv.29300
|View full text |Cite
|
Sign up to set email alerts
|

Use of immuno assays during the development of aHemophilus influenzaetypebvaccine for technology transfer to emerging vaccine manufacturers

Abstract: Quality control of Hemophilus Influenzae type b (Hib) conjugate vaccines is mainly dependent on physicochemical methods. Overcoming sample matrix interference when using physicochemical tests is very challenging, these tests are therefore only used to test purified samples of polysaccharide, protein, bulk conjugate, and final product. For successful development of a Hib conjugate vaccine, several ELISA (enzyme-linked immunosorbent assay) methods were needed as an additional tool to enable testing of in process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Hib PRP antigens were conjugated to TT, and ELISA used to assess if the PRP was pure and if the two components were successfully linked. It was found that ELISA was suitably precise and cheap for use as a test by others for similar purposes (Hamidi & Kreeftenberg, 2014).…”
Section: Conjugate Productionmentioning
confidence: 99%
“…Hib PRP antigens were conjugated to TT, and ELISA used to assess if the PRP was pure and if the two components were successfully linked. It was found that ELISA was suitably precise and cheap for use as a test by others for similar purposes (Hamidi & Kreeftenberg, 2014).…”
Section: Conjugate Productionmentioning
confidence: 99%
“…That was also the case for residual reagents and residual reactive groups, initially nuclear magnetic resonance (NMR) was used but these tests can also be omitted after process validation. The identity of each bulk conjugate was tested using the antigenicity test . To test for the immunogenicity of the bulk conjugate, a mice immunogenicity test, was developed …”
Section: Development Strategy Followed For the New Hib Conjugate Vaccinementioning
confidence: 99%
“…The identity of each bulk conjugate was tested using the antigenicity test . To test for the immunogenicity of the bulk conjugate, a mice immunogenicity test, was developed …”
Section: Development Strategy Followed For the New Hib Conjugate Vaccinementioning
confidence: 99%
See 2 more Smart Citations